2006
DOI: 10.1002/qua.21235
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational dynamics of hydrogen‐bonded HCN complexes with OH and NH acids: Computational DFT systematic study

Abstract: Vibrational properties (band position, infrared [IR], and Raman intensities)of C'N stretching mode were studied in 65 gas phase hydrogen-bonded 1:1 complexes of HCN with OH acids and NH acids using density functional theory (DFT) calculations at the B3LYP-6-311ϩϩG(d,p) level. Furthermore, general characteristics of the hydrogen bonds and vibrational changes in acids OH/NH stretching bands were also considered. Experimentally observed blue shift of the C'N stretching band promoted by hydrogen bonding, which sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…EPN proved also a reliable reactivity index for chemical reactions 31, 32. The electrostatic potential at nuclei found recently further successful applications as a reactivity descriptor and provided solutions to various chemical problems 35–45…”
Section: Kinetic Experiments and Theoretical Computationsmentioning
confidence: 99%
“…EPN proved also a reliable reactivity index for chemical reactions 31, 32. The electrostatic potential at nuclei found recently further successful applications as a reactivity descriptor and provided solutions to various chemical problems 35–45…”
Section: Kinetic Experiments and Theoretical Computationsmentioning
confidence: 99%
“…[18] 2.2. IR and Raman Spectra 2-Hydroxybut-3-enenitrile 3 and 2-hydroxybut-3-ynenitrile 4 have never been studied by infrared spectroscopy and no full study hasb een reported for the simplest derivative 1 and lactonitrile 2.T heoretical calculations [19] and some studies in am atrix [6,20] have, however, been reported for compound 1.…”
Section: Uv Photoelectron Spectramentioning
confidence: 99%